A dipyrrole derivative from Aloe vera inhibits an anti-diabetic drug target Dipeptidyl Peptidase (DPP)-IV in vitro. Issue 5 (4th May 2020) - Prasannaraja, C.; Kamalanathan, A. S.; Vijayalakshmi, M. A.; Venkataraman, Krishnan
Abstract: Aloe vera, a succulent herb, has a long history of use in traditional medicine, including diabetes. Earlier studies from our laboratory demonstrated that the Aloe vera extract has the ability to inhibit the diabetic drug target dipeptidyl peptidase (DPP) IV in vitro . This current study focuses on the isolation of small water soluble active molecule(s) involved in DPP-IV inhibition from Aloe vera extract, and further to characterize its structure and to elucidate the mode of inhibition of the DPP-IV enzyme. Aloe vera gel ethanolic extract was subjected to preparative reverse-phase high-pressure liquid chromatography (RP-HPLC), LH-20 Sephadex gel filtration chromatography, followed by analytical RP-HPLC, to isolate the active molecule involved in DPP-IV inhibition. Based on the spectroscopic studies, the structure of the isolated DPP-IV inhibitor was predicted to be 3, 6-dioxo-3, 3a, 6, 6 a-tetrahydropyrrolo [3, 4-c] pyrrole-1, 4-dicarboxamide with the chemical formula C8H6N4O4, having the molecular weight of 225.175 Da. This molecule inhibited the DPP-IV enzyme in a noncompetitive manner with an IC50 value of 8.59 ± 2.61 µM, with a Ki of 4.7 ± 0.038 µM. Thus, the mechanism of DPP-IV inhibition and the inhibitory constants were determined. The results of our studies suggested that the inhibition of the DPP-IV enzyme as one of the pathways by which the Aloe vera extract may restore the pancreatic islets cell mass in diabetic animal model.